Alaskan rescue [large type] - Reed, Terri (Love inspired suspense., 2021)
Sent to find a wedding party that disappeared during a hike, Alaskan state trooper Hunter McCord and his K-9 partner, Juneau, discover bridesmaid Ariel Potter hanging from a cliff, But this was no accident - she was pushed - and her friends are missing. Hunter and Juneau must find them and protect Ariel.